Self-management Interventions for Pain and Physical Symptoms Among People Living With HIV: A Systematic Review of the Evidence. (1st October 2018) - Nkhoma, Kennedy; Norton, Christine; Sabin, Caroline; Winston, Alan; Merlin, Jessica; Harding, Richard
Abstract : Introduction: Pain and symptoms still persist among people living with HIV/AIDS. Evidence-based self-management interventions have the potential to help people with HIV/AIDS to successfully manage pain and symptoms. We aimed to identify and appraise the evidence regarding the effectiveness of self-management interventions for pain and/or physical symptoms in people living with HIV/AIDS. Methods: We searched for controlled intervention studies in Amed, Assian, CINAHL, Cochrane Library, Embase, Medline, PsycInfo, Scopus, and Web of Science data bases, from 1984 to February 2017. Two reviewers screened and extracted data, assessed risk of bias (using Joanna Briggs Institute Critical Appraisal checklist for randomized and nonrandomized trials), and rated the quality of evidence (GRADE tool). Results: We identified 22 original papers reporting 19 different studies. Of these, 17 used randomized controlled trial designs. Three studies reported data on pain severity, and 2 studies reported data on pain interference outcomes with one study reporting positive effect on both outcomes. Outcomes for physical symptoms were reported in 13 studies with 6 studies reporting positive effect. The quality of evidence was moderate for pain outcomes. For physical symptoms, one study was rated as moderate; the rest were rated as low n = 8 and very low n = 4 quality. Conclusions: There is some evidence to suggest that self-management interventions delivered either online, face-to-face, or group-based consisting of booklet, leaflet, or manuals are effective in improving pain and physical symptoms. Findings suggest the need for theoretically plausible high-quality clinical trials of pain and physical symptom self-management among culturally diverse people with HIV.